Climate, settlement patterns and olive horticulture in the southern Levant during the Early Bronze and Intermediate Bronze Ages (c. 3600–1950 BC). (3rd May 2016) - Langgut, Dafna; Adams, Matthew J.; Finkelstein, Israel
Abstract : We report results of palynological investigation of a core of sediments extracted from the bottom of the Sea of Galilee. The core was sampled at high resolution for both palynological analysis (a sample was taken c. every 40 years) and radiocarbon dating. The article focuses on the Early Bronze and Intermediate Bronze Ages, c. 3600–1950 BC. The results enable reconstruction of the vegetation and thus climate in the lake's fluvial and alluvial catchment, which includes large parts of northern Israel and Lebanon and south-western Syria. The study sheds light on topics such as changes in olive cultivation through time and regions, processes of urbanization and collapse and settlement expansion and retraction in the arid zones.